Estudo de técnicas de controle aplicadas ao conversor SEPIC para correção do fator de potência em um LED driver - Thiago Marques de Souza (2016)
Light emitting diodes (LEDs) have become a viable technological alternative for improving the efficiency of the illumination systems. However, the LEDs have a peculiarity in their operation, since they must be driven in current. In this sense, this thesis presents the design and modeling of a two-stage LED driver, the main converter being based on a buck and the power factor correction (PFC) in a SEPIC converter in the Discontinuous operation mode (DCM). A comparative analysis between two control techniques is performed for the SEPIC PFC in DCM. The first one applies the classic linear approach to regulating the control loop. In the second technique, this regulation is performed through the state feedback linearization (SFL) of the average model of the d.c.-d.c. converter in state space. In order to compare the performance of these control techniques, numerical simulations were performed of a 100W LED driver in the PSIM software for both the nominal conditions and for disturbances in the operation, analyzing the power factor (PF) on the a.c. side, the harmonic distortion (THD) of the input current and d.c. side voltage regulation. In addition, computational results are obtained from the high-level programming with the integration Matlab/DSP and Hardware In the Loop (HIL).